2014
DOI: 10.5267/j.msl.2014.3.004
|View full text |Cite
|
Sign up to set email alerts
|

A study on relationship between dividend changes with future profitability

Abstract: This paper studies the relationship between dividend changes and future profitability of listed companies in Tehran Stock Exchange. Using the information of 191 companies, the study has implemented some regression techniques. The results of the research model analysis indicate that the changes in dividend contain significant and important information content, for the future profitability and dividend changes, and have an important and positive impact on the future profitability of the company. The results also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The analyzes conducted by Ghodrati and Hashemi (2014) for companies from Iran show in turn that the impact of the increase in dividends on the future profitability of companies measured by ROE is positive in the next three years (+1, +2, +3) but statistically significant only in the first year. However, in the case of dividend reductions, the authors do not confirm the existence of specific links between ROE and dividend changes.…”
Section: Informational Content Of Dividends In the Polish Capital Marketmentioning
confidence: 99%
“…The analyzes conducted by Ghodrati and Hashemi (2014) for companies from Iran show in turn that the impact of the increase in dividends on the future profitability of companies measured by ROE is positive in the next three years (+1, +2, +3) but statistically significant only in the first year. However, in the case of dividend reductions, the authors do not confirm the existence of specific links between ROE and dividend changes.…”
Section: Informational Content Of Dividends In the Polish Capital Marketmentioning
confidence: 99%
“…In particular, S. P. Lee, M. Isa and W. L. Lim (2012) for the Malaysian stock market found that changes in dividends (increase / decrease) must be significant (by 50% or more) to bring a specific EPS signal, though the range of this signal was limited to the first year after the change. Analyses by H. Ghodrati and A. Hashemi (2014) conducted for companies in Iran, showed that the impact of the dividend growth on the future profitability (ROE) was positive in the next three years but statistically significant only in the first year. For reduced dividends, the authors did not confirm the signaling hypothesis.…”
Section: Current Dividends and Future Profits -A Review Of The Literamentioning
confidence: 99%
“…In particular, the results of the studies by Lee and others (2012), conducted on the stock market in Malaysia indicated that the changes in dividends (an increase/a decrease) must be of a substantial size (by 50% or more) to carry a specific signal about the future profits (the EPS was used as a measure of profit), although the scope of this signal was limited to only one year after the changes. In turn, analyses of Ghodrati and Hashemi (2014), conducted for the companies from Iran, showed that an impact of a dividend increase on the future profitability of the companies (the ROE was used as a measure of profit) was positive in the next three years (+1, +2, +3) but statistically significant only in the first year. However, in the case of a dividend reduction, the authors did not confirm the occurrence of dependences relevant to the signalling hypothesis.…”
Section: The Current Changes In a Dividend Level And The Future Resulmentioning
confidence: 99%